Penerapan Model Pembelajaran Grup Investigation (GI) Berbantuan Vidio Pembelajaran Untuk Meningkatkan Hasil Belajar IPA - I Ketut Hariawan (Jayapangus Press, 2020)
This action research aims: (1) to improve the science learning outcomes of VIIA class students in the even semester of SMP Negeri 1 Manggis in the academic year 2017/2018 by applying the learning investigation (GI) learning model assisted by learning videos. This type of research is classroom action research. The subjects of this study were 30 students in class VIIA, and the object of this study was the science learning outcomes. This action research is planned to be carried out in two cycles. Learning outcomes data were collected using multiple choice tests. Data were analyzed by descriptive analysis. The results showed that: (1) The natural science learning outcomes of the VIIA class in the second semester increased in the first cycle by an average of 70, 70% absorption, with a 50% grade completeness, and an average cycle II of 77, 77 absorption %, with 86.6% class completeness. With the achievement of an average of 77 Natural Science learning outcomes, it means that it is above the established success level of 70, so that the action is considered successful. Thus it can be said that the application of the learning investigation (GI) group learning model assisted by learning videos can improve the learning outcomes of natural science students in class VIIA an even number at SMPN 1 Manggis in the academic year 2017/2018.